Cele wykonywania kary pozbawienia wolności a instytucja warunkowego przedterminowego zwolnienia uwagi na marginesie uchwały Sądu Najwyższego z dnia 26 kwietnia 2017 r., I KZP 2/171 - Kania, Agnieszka (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
This article brings attention not only to the need for a distinction between penalty and its functions, but also to the nature of the tasks posed before the penalty at the stage of imposing and executing the penalty. Based on the example of imprisonment, it has been proven that at the stage of execution the assigned to it objectives become limited to the completion of the reasons of the individual-preventive nature. Further part of this study also relates to the Supreme Court resolution of 26 April 2017, which accurately pointed out that while adjudicating release on licence from the rest of the sentence, criminal purposes, present at the stage of imposing the penalty referred to in chapter VI of the Criminal Code, must yield to individual-preventive reasons.
Keywords: purposes of punishment; release on licence; judicial sentencing